Code as information and code as spectacle. Issue 2 (2nd July 2016) - Roberts, Charles
ABSTRACT: In this artist statement, I will discuss the tension between source code as an interactive system for performers and source code as information and entertainment for audiences in live-coding performances. I then describe augmentations I developed for the presentation of source code in the live-coding environment Gibber, including animations and annotations that visually reveal aspects of system state during performances. I briefly describe audience responses to these techniques and, more importantly, how they are critical to my own artistic practice.